Elite Athletes’ Perfectionistic Striving vs. Concerns as Opposing Predictors of Self-Handicapping With the Mediating Role of Attributional Style - Török, Lilla; Szabó, Zsolt Péter; Orosz, Gábor (Frontiers in Psychology, 2022)
Self-handicapping is not only present among amateurs, but even among the most elite athletes. The vast majority of the research investigates self-handicapping in academic context among students with mediocre performance. However, scientific examinations of predictors among top performers in the field of sports is terra incognita. Among the predictors of self-handicapping, perfectionistic strivings and concerns as well as attributional style, were demonstrated as relevant ones among samples in prior studies. However, these links have never been examined among elite athletes who can be characterized by various aspects of perfectionism. In this study, the link between self-handicapping and perfectionistic striving and concerns was examined both directly and indirectly through the potential mediating effect of attributional style among elite athletes (N=111) where more than half of the participants was competing at international level such as European and World Championships or Olympic Games. As it was expected, a positive relationship was found between perfectionistic concerns and self-handicapping, whereas the findings suggested a negative relationship between perfectionistic striving and self-handicapping. These connections were partially mediated by attributions for negative sport-related events. It appears that explanations for negative events are crucial in connection with protecting oneself through self-handicapping even among top athletes. The present work is a first step of a broader program in which the goal is reducing self-handicapping of top athletes through attributional retraining intervention.